Letter from Carl D. Duncan to Patricia Whiting, February 11, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan recalls a conversation with Whiting's mother and asks Whiting to take his mail to his apartment while he is in Portland.